Advanced Processing Technologies for Innovative Materials - Sergey N. Grigoriev; Marina A. Volosova; Anna A. Okunkova (Technologies, 2024)
There is a need for further, in-depth research that explores the synthesis of newly developed materials created using advanced technologies [...]